Evaluasi Kinerja Karyawan PT. XYZ dengan Pendekatan Metode Fuzzy Mamdani - Muharni Muharni; Widiarti Awaliah; Dewi Fatmawati Surianto (Indonesian Technology and Education Journal, 2025)
Employee performance evaluation is vital for organizational effectiveness, ensuring fair and objective assessments. PT. XYZ, a cement distributor, struggles with subjective evaluation criteria, prompting the need for a more accurate approach. This study applies the Fuzzy Mamdani method to improve performance assessment. Data from 31 employees were collected through literature reviews, interviews, and observations. The system uses salary, age, and years of service as input variables, while the output variable represents employee performance. The Fuzzy Mamdani method processes data through fuzzification, fuzzy inference, and defuzzification to handle uncertainty and enhance evaluation fairness. The results show that 29 employees fall under the "Good" performance category, while 2 employees are classified as "Very Good." This demonstrates that the method provides more precise and consistent assessments compared to traditional techniques. Implementing this approach enables companies to make better-informed human resource decisions and promote employee growth. This study underscores the potential of fuzzy logic in refining performance evaluations, contributing to a more transparent and equitable assessment system